(untitled) (Siddhajyoti Interdisciplinary Journal, 2026)
This paper investigates the sociolinguistic dimensions of gender and language through a comparative analysis of four major European languages: English, Spanish, Italian, and French. Drawing on interdisciplinary research in linguistics, gender studies, and language policy, the review examines how grammatical gender systems, lexical choices, pronoun usage, and media representations construct, reinforce, and reflect gender norms. The study synthesizes key empirical findings and theoretical perspectives to highlight both structural and cultural differences in how these languages encode gender and reproduce social hierarchies. The study highlighted that, while English has largely abandoned grammatical gender, its pronoun system and discursive practices continue to reflect gendered ideologies, with recent reforms toward gender-neutral pronouns illustrating how language evolves alongside sociopolitical change. In contrast, Spanish, Italian, and French maintain robust grammatical gender systems, where masculine-default forms persist in mixed-gender contexts but are increasingly contested through inclusive writing practices and public debate. This analysis underscores that gendered language is not merely a reflection of grammar but a dynamic sociocultural phenomenon shaped by activism, policy, and media discourse. The paper argues that developing critical sociolinguistic awareness is essential for understanding the intersections of language, identity, and power, offering implications for more inclusive language education, progressive policy frameworks, and equitable representation in multilingual societies.